Achieving stable and efficient water oxidation by incorporating NiFe layered double hydroxide nanoparticles into aligned carbon nanotubes. Issue 2 (15th January 2016) - Chen, Rong; Sun, Gengzhi; Yang, Cangjie; Zhang, Liping; Miao, Jianwei; Tao, Huabing; Yang, Hongbin; Chen, Jiazang; Chen, Peng; Liu, Bin
Abstract : Binder-free hybrid microfiber electrodes with excellent oxygen evolution reaction activity were fabricated by scrolling stable dispersed NiFe-LDH nanoparticles into well-aligned multi-walled carbon nanotubes. Abstract : A facile and scalable co-precipitation method is developed to prepare stable colloidal NiFe-LDH nanoparticles at room temperature. We further scrolled NiFe-LDH nanoparticles into well-aligned multi-walled carbon nanotube (MWCNT) sheets to form binder-free hybrid microfiber electrodes, which showed excellent OER activity, reaching 180 mA cm −2 at a small overpotential of 255 mV with outstanding durability.